2019
DOI: 10.1002/mmce.21973
|View full text |Cite
|
Sign up to set email alerts
|

Tunable dual band antenna with multipattern reconfiguration for vehicular applications

Abstract: This article presents the design of a pattern switchable patch antenna for vehicular applications. The proposed antenna has a square patch that is divided into four triangular regions using diagonal rows of vias. The triangular regions are separately excited using a coaxial feed to achieve frequency and pattern reconfiguration. Each triangular section of the antenna has “U” shaped and inner rectangular strips to obtain two resonant frequencies of 2.4 and 3.5 GHz, respectively to cover the part of WLAN, WiMax, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…It is found that the highest efficiency of an antenna is 83%, and 81% for the range of 2.4‐2.66 and 3.31‐3.57 GHz, respectively. Larger bandwidth coverage of 270 and 360 MHz at 2.4‐ and 3.5‐GHz band, respectively, when compared to a narrow operating bandwidth of fewer than 200 MHz was reported in References , , , and The efficiency reported in this research work is 83% which is higher than the efficiency reported in References , , , , and . A total of 16 different beams are produced by the proposed antenna with reduced complexity; however, the research work reported in References and gives a maximum of eight beams with increased numbers of active elements and patches. The maximum gain achieved by this antenna is 10.7 and 9.8 dBi at 2.4‐ and 3.5‐GHz band, respectively; however, the maximum gain reported in References , , , , and are less than 9 dBi. The design of antennas integrating multiple features, such as high gain, multiband, wide bandwidth, directive radiation, multiple radiation patterns for omnicoverage, low cost, and less complex structure, is of increasing demand for vehicular communication. This antenna satisfies all these requirements by using low‐cost FR4 dielectric material as substrate for reducing manufacturing cost, the multiple radiation patterns are realized from simple multiport excitation technique, high gain is attained by etching dual SR slots at the ground plane with the addition of reflector and hence this antenna is useful for high throughput satellite as well as base station‐enabled data services. …”
Section: Measurement Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…It is found that the highest efficiency of an antenna is 83%, and 81% for the range of 2.4‐2.66 and 3.31‐3.57 GHz, respectively. Larger bandwidth coverage of 270 and 360 MHz at 2.4‐ and 3.5‐GHz band, respectively, when compared to a narrow operating bandwidth of fewer than 200 MHz was reported in References , , , and The efficiency reported in this research work is 83% which is higher than the efficiency reported in References , , , , and . A total of 16 different beams are produced by the proposed antenna with reduced complexity; however, the research work reported in References and gives a maximum of eight beams with increased numbers of active elements and patches. The maximum gain achieved by this antenna is 10.7 and 9.8 dBi at 2.4‐ and 3.5‐GHz band, respectively; however, the maximum gain reported in References , , , , and are less than 9 dBi. The design of antennas integrating multiple features, such as high gain, multiband, wide bandwidth, directive radiation, multiple radiation patterns for omnicoverage, low cost, and less complex structure, is of increasing demand for vehicular communication. This antenna satisfies all these requirements by using low‐cost FR4 dielectric material as substrate for reducing manufacturing cost, the multiple radiation patterns are realized from simple multiport excitation technique, high gain is attained by etching dual SR slots at the ground plane with the addition of reflector and hence this antenna is useful for high throughput satellite as well as base station‐enabled data services. …”
Section: Measurement Resultsmentioning
confidence: 53%
“…However, additional complex reconfiguration structures are used with more number of parasitic elements to realize pattern reconfiguration. The researchers in References and use diagonal lines of vias to divide the square patch into four triangular regions with each having their own edge excitation to generate 12 different beams. However, the antenna has narrow bandwidth of operation suitable for Internet of Things (IoT) applications.…”
Section: Introductionmentioning
confidence: 99%
“…The comparison between the gain realized by an antenna without FSS superstrate, with single and double FSS superstrate layers is shown with the parametric study of every beam. Larger bandwidth coverage of 280 MHz, 270 MHz at 2.4 and 3.5 GHz band, respectively, which is higher on comparing to the bandwidth reported in papers , , , The efficiency reported in this research work is 86% while the efficiency reported in papers, , , , , are less than 75%. A total of 14 different beams are produced by the proposed antenna, however, the antennas reported in papers, , , generates a maximum of four beams with increased complexity. A novel ultrathin FSS of thickness 0.381 is proposed in this work, whereas in papers the conventional FSS structure made of the thick substrate is reported. The frequency tuning plays a vital role in widening the bandwidth coverage of wireless communication. However such tuning is not reported in References and . The antenna reported in this article operates in both WLAN, WiMax bands.…”
Section: Measurement Resultsmentioning
confidence: 67%
“…e antenna maintained stable gain ranging from 7.1 to 7.65 dBi over the whole operating band. Various designs of MIMO antennas and techniques, reconfigurable, tunable, and array antennas for different applications, are presented in [12][13][14][15][16][17][18][19][20]. A U-slot microstrip patch antenna for the 28 GHz band is presented in [21].…”
Section: Introductionmentioning
confidence: 99%